Increased Expression of Circulating microRNA 101-3p in Type 1 Diabetes Patients: New Insights Into miRNA-Regulated Pathophysiological Pathways for Type 1 Diabetes - Santos, Aritania S.; Cunha Neto, Edecio; Fukui, Rosa T.; Ferreira, Ludmila R. P.; Silva, Maria Elizabeth R. (Frontiers in Immunology, 2019)
MicroRNAs (miRs) are master regulators of post-transcriptional gene expression, and are dysregulated in diabetes. We investigated the roles of miR-101-3p and miR-204-5p, which negatively regulate insulin secretion and cell survival and are highly expressed in pancreatic β cells, in type 1 diabetes (T1D) pathogenesis. Using quantitative real time PCR, we evaluated serum levels of miR-101-3p and miR-204-5p in four groups: recent-onset T1D patients (T1D group; n = 50), individuals with normal glucose levels expressing one islet autoantibody(Ab) (single Ab group; n = 26) or multiple autoantibodies (multiple Ab group; n = 12), and healthy controls (control group; n = 43). An in silico analysis was performed to identify potential target genes of these miRNAs and delineate enriched pathways. The relative expression of serum miR-101-3p was approximately three times higher in the multiple Ab and T1D groups than that in the single Ab and control groups (p < 0.0001). When considering all groups together, miR-101-3p expression was positively correlated with the level of islet autoantibodies GADA (r = 0.267; p = 0.0027) and IA-2A (r = 0.291; p = 0.001), but not with the levels of ZnT8A (r = 0.125; p = 0.183). miR-101-3p expression did not correlate with HbA1c (r = 0.178; p = 0.052) or glucose levels (r = 0.177; p = 0.051). No significant differences were found in miR-204-5p expression among the analyzed groups. Computational analysis of the miR-101-3p target gene pathways indicated a potential activation of the HGF/c-Met, Ephrin receptor, and STAT3 signaling pathways. Our study shows that the circulating levels of miR-101-3p are higher in T1D patients and in individuals with normal glucose levels testing positive for multiple autoantibodies, indicating that miR-101-3p precedes loss of glucose homeostasis. The pathogenic role of miR-101-3p in T1D may involve multiple molecular pathways.